A compact, dual wide-band circularly polarized, modified square ring slot antenna for C and Ku band applications. Issue 2 (1st October 2018) - Patil, Shilpee; Singh, Anil Kumar; Kanaujia, Binod Kumar; Yadava, R. L.
Abstract: This paper presents a compact microstrip antenna using FR-4 substrate for dual band circularly polarized operation using a modified square ring slot in the ground plane with microstrip line feed. Simulation of the impedance characteristic and radiation characteristic for the proposed antenna is carried out using commercially available HFSS software. The simulated data validate measured results and shows good agreement. Proposed antenna shows an impedance bandwidth (return loss >10 dB) of 50.88% at 5.9 GHz of center frequency and 29.92% at 12.8 GHz of center frequency for lower and upper band, respectively. The 3 dB axial ratio bandwidth for lower and upper band is 26.4 and 3.0%, respectively and measured peak gain for the lower and upper band is found as 3.2 and 3.4 dBic, respectively. The proposed antenna can be suitable for wireless communication in C and Ku bands.